Hürthle Cell Carcinoma: Single Center Analysis and Considerations for Surgical Management Based on the Recent Literature - Chiapponi, Costanza; Hartmann, Milan J.M.; Schmidt, Matthias; Faust, Michael; Bruns, Christiane J.; Schultheis, Anne M.; Alakus, Hakan (Frontiers in Endocrinology, 2022)
Background: Hürthle cell carcinoma (HCC) of the thyroid is rare. There are contrasting data on its clinical behavior. The aim of this study was to describe clinic-pathological features and outcomes of HCC patients at our institution, in order to adapt our surgical management. Methods: We retrospectively studied 51 cases of HCC treated at the interdisciplinary endocrine center of the University Hospital of Cologne, Germany between 2005 and 2020. Results: Patients median age was 63 years (range 29-78) with 64.7% of cases being female. Primary treatment included surgery and postoperative radioiodine therapy with 3.7 GBq in all patients. Surgery consisted of total thyroidectomy in all cases and additional central lymphadenectomy in 90.2% of cases. The median number of harvested lymph nodes was 11 (range 2-31). Lymph node involvement was found in two (4.3%) pT4a tumors. In all other cases (95.7%) central lymphadenectomy was prophylactic and lymph nodes were free of metastasis in final histopathology. Twelve (23.5%) patients with incomplete biochemical response to primary treatment were diagnosed with structural relapse during the course of disease, for which seven (58.4%) underwent resection of isolated cervical metastasis. Histopathology revealed soft tissue implants in all cases and cervical surgery led to biochemical and radiologic cure in only two (28.5%) cases. Five (41.6%) patients developed metastatic disease, followed by systemic therapy in two patients. Vascular invasion of the primary tumor was significantly associated with relapse (p<0.01). Conclusions: Recurrence of HCC was common in this study. Given the low rate of lymph node metastases both in this study and in recent literature and the nature of relapse (soft tissue instead of nodal metastasis), the benefit of routine prophylactic central lymph node dissection for HCC remains unclear, especially in the absence of vascular invasion from the primary tumor.